Militares, cortesanos y poetas en el entorno de los infantes de Aragón (1439-1445): las Coplas de Juan de Dueñas al infante don Enrique. - RUBIO VELA, AGUSTÍN (Scripta, 2017)
The Coplas de Juan de Dueñas al infante don Enrique, a Castilian poem of the 15th century, is a historical source of notable interest to explore the military environment of the time, as well as the court and literary world of John of Navarra, who would later become John II of Aragon. An analysis of its contents, in the light of contemporary chronicles and documents, reveals it must have been written in Castile between 1440 and 1443; that is, prior to the defeat of the Infantes of Aragon in Olmedo.